(untitled) (E Conference Zone, 2022)
There is a growing need for institutions to provide assistance to victims of violence. In order to improve the system of social rehabilitation in Uzbekistan, the Republican Center for Rehabilitation and Adaptation of Victims of Violence was established by the Presidential Decree of July 2, 2018